Genetic analysis in three Egyptian patients with Griscelli syndrome Type 1 reveals new nonsense mutations in MYO5A. (10th April 2020) - Abd Elmaksoud, M. S.; Gomaa, N. S.; Azouz, H. G.; On, C. N. V.; Ho, C. T.; Omar, T. E.; McGrath, J. A.; Onoufriadis, A.
Abstract : Click here for the corresponding questions to this CME article.